Customs, Trinidad, B.W.I. - (:unkn) unknown (My University, 2011)
A picture of Trinidad's wharf. In this picture you can see the customs building and a pier.
Colour: Black and White; Style: Landscape; Other: Bordered, Undivided.
Keywords: Trinidad and Tobago; Postcards; Harbors--Trinidad and Tobago; Customhouses--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Piers--Trinidad and Tobago